Commodity Price Dynamics and Islamic Stock Market Volatility in Indonesia - Hakiki Ramadhan; Muhammad Hasanuddin; Anisa Ilmia; Lidzikri Ahmad Syahru Rabbani (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
Amid increasing integration between global commodity markets and emerging Islamic capital markets, understanding volatility transmission has become critical for risk management and policy design. This study investigates how volatility from Brent crude oil, gold, and crude palm oil (CPO) influences the Indonesian Sharia Stock Index (ISSI) from October 2022 to October 2024. The analysis uses daily data (N = 484) and employs GARCH and EGARCH frameworks to capture time-varying volatility, spillovers, and asymmetric responses to shocks. ARCH-LM tests confirm conditional heteroskedasticity in ISSI and USD/IDR returns, while EGARCH(1,1) models are also estimated for all variables to consistently account for asymmetry. Conditional volatility series are derived and examined to identify inter-market transmission effects. The results reveal that USD/IDR plays a dominant role, affecting gold negatively and CPO positively, reflecting the dual nature of commodities as safe-haven and export assets. Geopolitical risk significantly influences only Brent oil, suggesting a degree of insulation in Sharia equities. Strong leverage effects are observed in ISSI and CPO, where negative shocks amplify volatility more than positive ones, and CPO shows heavy-tail risk. Although commodity variables and geopolitical risk do not significantly explain ISSI returns, its volatility remains asymmetric, indicating stronger domestic drivers. These findings highlight the importance of exchange rate dynamics, asymmetric risk modeling, and commodity sensitivity in Islamic portfolio management, while offering implications for hedging strategies and macroprudential policy in open emerging economies. ABSTRAK - Dinamika Harga Komoditas dan Volatilitas Pasar Saham Syariah di Indonesia. Seiring meningkatnya keterkaitan antara pasar komoditas global dan pasar modal syariah di negara berkembang, pemahaman tentang transmisi volatilitas menjadi semakin penting bagi pengelolaan risiko dan perumusan kebijakan. Studi ini menganalisis pengaruh volatilitas minyak Brent, emas, dan crude palm oil (CPO) terhadap Indeks Saham Syariah Indonesia (ISSI) selama periode Oktober 2022 hingga Oktober 2024. Dengan menggunakan data harian (N = 484), penelitian ini mengadopsi pendekatan GARCH dan EGARCH untuk menangkap dinamika volatilitas, efek spillover, serta respons asimetris terhadap guncangan pasar. Uji ARCH-LM menunjukkan adanya heteroskedastisitas bersyarat pada ISSI dan nilai tukar USD/IDR, sementara model EGARCH(1,1) digunakan secara konsisten untuk seluruh variabel guna mengakomodasi asimetri. Volatilitas kondisional yang dihasilkan kemudian dianalisis untuk mengidentifikasi transmisi antar pasar. Hasil menunjukkan bahwa USD/IDR menjadi faktor dominan dengan dampak negatif pada emas dan positif pada CPO, mencerminkan perbedaan peran komoditas sebagai aset lindung nilai dan komoditas ekspor. Risiko geopolitik hanya berpengaruh signifikan pada minyak Brent, mengindikasikan adanya ketahanan relatif pada pasar saham syariah. Efek leverage yang kuat ditemukan pada ISSI dan CPO, di mana berita buruk meningkatkan volatilitas secara lebih tajam, serta CPO menunjukkan risiko ekor yang tinggi. Meskipun variabel global tidak menjelaskan return ISSI secara signifikan, volatilitasnya tetap asimetris, menandakan peran faktor domestik. Temuan ini memberikan implikasi bagi manajemen portofolio syariah, strategi lindung nilai, dan kebijakan makroprudensial.